Vegetation structure, microclimate, and edaphic variables as determinants of macrofungi occurrence in the Maros-Pangkep Karst Area, Indonesia - ALI HASAN SALMAN; MUHAMMAD RESTU; SITI HALIMAH LAREKENG; RETNO PRAYUDYANINGSIH (Society for Indonesian Biodiversity, 2026)
Abstract. Salman AH, Restu M, Larekeng SH, Pryudyaningsih R. 2026. Vegetation structure, microclimate, and edaphic variables as determinants of macrofungi occurrence in the Maros-Pangkep Karst Area, Indonesia. Biodiversitas 27 (3): d270303. https://doi.org/10.13057/biodiv/d270303. The Maros-Pangkep karst region in South Sulawesi, Indonesia, is known as the second largest karst in the world with a unique tower karst landscape and high biodiversity, including macrofungi. This study aimed to analyze the relationship between the presence of macrofungi and edaphic, microclimate, and vegetation factors to deepen the understanding of fungal ecology. Field surveys were conducted across 15 sampling plots representing different vegetation conditions. Macrofungi composition was recorded alongside measurements of microclimate variables (air temperature, humidity, light intensity) and edaphic properties (soil moisture, pH, organic carbon, total nitrogen, and available phosphorus). A total of 52 macrofungi species, belonging to 35 genera and 24 families, were documented, with Polyporaceae as the most dominant family. Species richness and diversity indices varied among plots, reflecting differences in vegetation complexity and environmental conditions. Principal Component Analysis (PCA) indicated that air humidity and soil moisture were the strongest variables associated with macrofungi occurrence, while higher temperature and light intensity showed negative associations. Edaphic factors, particularly soil moisture and organic carbon, contributed more strongly to macrofungi abundance than soil nutrient concentrations. Vegetation structure, especially sapling density and herbaceous cover, was associated with macrofungi abundance, whereas tree density was more closely related to species richness. These results demonstrate that macrofungi occurrence in karst ecosystems is shaped by the interaction of microclimatic conditions, soil properties, and vegetation structure rather than by single environmental drivers. The study highlights the importance of maintaining humid microhabitats and heterogeneous vegetation to support macrofungi diversity in karst landscapes. These findings provide a deeper understanding of macrofungi ecology and serve as an important basis for identifying macrofungi species with potential for utilization in various fields.